2020
DOI: 10.1177/1609406920967868
|View full text |Cite
|
Sign up to set email alerts
|

Using Dyadic Interviews to Explore Recovery as Collaborative Practices: Challenging the Epistemic Norm of the Single Person Perspective

Abstract: The method dyadic interviews involves interviewing a pair of participants, focusing explicitly on the interaction between them and how it develops data. Dyadic interviews with persons who are involved in ongoing, working relationships can be a feasible means of exploring research topics that are related to collaboration and collaborative practices. The concept of recovery is considered highly relevant to different kinds of relationship-based practices, involving a person and context centered shift within the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…What follows is a brief outline of the power relationships that might present between two members of a dyad. It is widely acknowledged that one possible way to neutralize the power dynamic is by asking the participant to identify and invite the person they considered most helpful [12,30]. At the same time, power relationships within families (parent and child) seem inevitable.…”
Section: Dyadic Interviewmentioning
confidence: 99%
See 1 more Smart Citation
“…What follows is a brief outline of the power relationships that might present between two members of a dyad. It is widely acknowledged that one possible way to neutralize the power dynamic is by asking the participant to identify and invite the person they considered most helpful [12,30]. At the same time, power relationships within families (parent and child) seem inevitable.…”
Section: Dyadic Interviewmentioning
confidence: 99%
“…Food choice involves an isolated choice, but what a person decides to eat and how they arrive at a decision is often a form of collaborative decision with others in everyday life, for example, significant others, family members, or work [11]. It has been suggested that the use of dyadic interviews in exploring research topics related to collaboration can contribute to the co-creation of new knowledge [12].…”
Section: Introductionmentioning
confidence: 99%
“…This also includes how social conditions, inequity, and marginalization related to such issues affect people's lives and possibilities [19][20][21]. With its subjective, collaborative, and relational nature, recovery can be understood as a dynamic and open concept that cannot be "implemented" in services [15,22,23]. More specifically, in a research context, this could be perceived as shifting the focus from aiming to define what recovery is to describing and exploring how it can be understood in terms of personal and social contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Based in different traditions and practices and having different goals, this broad division of definitions implies that in understanding recovery and recovery-orientation, there is a need to clarify from which position one is speaking. In this study, we position our understanding of recovery and recovery orientation of services within a critical mental health paradigm in line with the social justice roots of the original recovery movement (Beresford et al, 2016 ; Davidson, 2016 ; Klevan et al, 2020 ; Pilgrim, 2009 ; Rose, 2014 ). In a broader perspective, the original recovery movement paradigm can also be seen as part of the de-institutionalization that has characterized mental health and substance abuse services in the Western world since the 1950s (Davidson, 2021 ; Topor et al, 2016 ).…”
mentioning
confidence: 97%
“…(Hansen et al, 2020 ; Reid et al, 2020 ; Topor, 2021 ; Topor et al, 2011 ). Within the context of community services, developing helpful strategies that can support the service user in resuming a meaningful life and valued roles involves a relationship with professional helpers based on core values such as role-blurring, balancing of power, and exchange and negotiation of skills, expertise, and various types of knowledge (Klevan et al, 2020 ; Ness et al, 2014 ). Rather than being perceived as “expert/helper” and “help-receiver,” professionals and service users are considered collaborators, working together in a dynamic relationship, where they co-produce knowledge and practices about recovery and helpful help in each unique case based on a variety of expertise and experiences (Kidd et al, 2016 ; Klevan et al, 2020 ; Ness et al, 2014 ).…”
mentioning
confidence: 99%